Long‐term survival of participants in the CENTAUR trial of sodium phenylbutyrate‐taurursodiol in amyotrophic lateral sclerosis. Issue 1 (30th October 2020) - Paganoni, Sabrina; Hendrix, Suzanne; Dickson, Samuel P.; Knowlton, Newman; Macklin, Eric A.; Berry, James D.; Elliott, Michael A.; Maiser, Samuel; Karam, Chafic; Caress, James B.; Owegi, Margaret Ayo; Quick, Adam; et al.
Abstract: An orally administered, fixed‐dose coformulation of sodium phenylbutyrate‐taurursodiol (PB‐TURSO) significantly slowed functional decline in a randomized, placebo‐controlled, phase 2 trial in ALS (CENTAUR). Herein we report results of a long‐term survival analysis of participants in CENTAUR. In CENTAUR, adults with ALS were randomized 2:1 to PB‐TURSO or placebo. Participants completing the 6‐month (24‐week) randomized phase were eligible to receive PB‐TURSO in the open‐label extension. An all‐cause mortality analysis (35‐month maximum follow‐up post‐randomization) incorporated all randomized participants. Participants and site investigators were blinded to treatment assignments through the duration of follow‐up of this analysis. Vital status was obtained for 135 of 137 participants originally randomized in CENTAUR. Median overall survival was 25.0 months among participants originally randomized to PB‐TURSO and 18.5 months among those originally randomized to placebo (hazard ratio, 0.56; 95% confidence interval, 0.34‐0.92; P = .023). Initiation of PB‐TURSO treatment at baseline resulted in a 6.5‐month longer median survival as compared with placebo. Combined with results from CENTAUR, these results suggest that PB‐TURSO has both functional and survival benefits in ALS.